2017
DOI: 10.1016/j.neuron.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Sox11 Expression Promotes Regeneration of Some Retinal Ganglion Cell Types but Kills Others

Abstract: SUMMARY At least 30 types of retinal ganglion cell (RGC) send distinct messages through the optic nerve to the brain. Available strategies of promoting axon regeneration act on only some of these types. Here we tested the hypothesis that over-expressing developmentally important transcription factors in adult RGCs could reprogram them to a “youthful” growth-competent state and promote regeneration of other types. From a screen of transcription factors, we identified Sox11 as one that could induce substantial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
165
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 47 publications
14
165
0
Order By: Relevance
“…For example, it was recently shown that SOX11, a known pro-regenerative transcription factor in the PNS 139 , can reprogramme adult non-α-RGCs to a growth-competent state. By contrast, SOX11 expression kills α-RGCs, the cellular subtype that preferentially regenerates following treatments such as PTEN deletion 143 . SOX11 expression also promotes CST regeneration after spinal cord injury but interferes with functional recovery 142 .…”
Section: Transcriptional Changesmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, it was recently shown that SOX11, a known pro-regenerative transcription factor in the PNS 139 , can reprogramme adult non-α-RGCs to a growth-competent state. By contrast, SOX11 expression kills α-RGCs, the cellular subtype that preferentially regenerates following treatments such as PTEN deletion 143 . SOX11 expression also promotes CST regeneration after spinal cord injury but interferes with functional recovery 142 .…”
Section: Transcriptional Changesmentioning
confidence: 98%
“…In addition to the previously highlighted transcription factors, several others — namely Myc proto-oncogene protein (MYC) 137 , hypoxia-inducible factor 1α (HIF1α) 138 , CREB1 (REFS 36,113 ), SOX11 (REFS 139143 ), TP53 (REFS 46,144 ), SRF48,145 and XBP1 (REFS 90,91 ) — have been identified to have roles in axon regeneration (see TABLE 1 and REFS 146,147 ). As little is known about the mechanisms by which these transcription factors are activated after injury, their regulation during development or their downstream targets, they will not be further discussed in detail here.…”
Section: Transcriptional Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sox11 can reprogram adult optic ganglion cells to a state with sufficient growth capacity, thereby promoting the regeneration of certain types of optic ganglion neurons . NEUROG2 and SOX11 synergistically convert human glioma cells into terminally differentiated neuron‐like cells in vitro and in adult mouse brain .…”
Section: Introductionmentioning
confidence: 99%